Forming creative approach to teaching - Грищенко, С. М. (Pedagogy of Higher and Secondary Education, 2013)
Grischenko S. M. Forming creative approach to teaching. The article highlights the problem of the creative teacher to the educational process and creative approach to teaching students in object-oriented computing environment.